Hysteresis Optimized Multipath TCP Data Scheduling Algorithm in Predictable Networks - Song, Zhaojie; Wu, Qian; Li, Hewu; Liu, Jun; Lai, Zeqi (International Wireless Communications and Mobile Computing Conference (Online), 2021)
The rapid development of high-speed rails (HSRs) has brought great convenience to people's travel. But related scholars found that the network status on the train is very inefficient. In order to solve that, some scholars proposed to use multipath TCP (MPTCP). However, MPTCP suffers when different paths have heterogeneous quality. In HSR scenarios, frequent handover (less than 10 seconds) occurs when devices connect to cellular network base stations. If MPTCP is used, each sub-flow has to go through handover and packets will be heavily garbled. In turn, it occupies a large amount of the receiver's buffer, even up to 100%. The latency of data submission to application will also be higher (10ms or more). It will affect the overall transfer performance. The reason for the above problem is that MPTCP does not react quickly enough to link changes and cannot accurately schedule packets between sub-flows. After consulting the measurement data of relevant scholars, we found that the trains in HSR have some recurring phenomena. For example, base station handover always occurs in the same place for devices in HSR. Based on relevant recurring information, this paper proposes Hysteresis Optimized Multipath TCP Data Scheduling Algorithm (HoMPTCP) in Predictable Networks. Combined with the prediction information formed by using historical trajectories in HSR, HoMPTCP can more accurately schedule packets between sub-flows and control the congestion window of sub-flows. After the experiments of HSR scenario, HoMPTCP can improve throughput performance by 5%-15% while increasing sequential arrival rate by 10%-15%.